2010
DOI: 10.1007/s10600-010-9522-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-association and complexation of triterpene glycosides and cholesterol

Abstract: hederacoside C) with cholesterol was studied using mass spectrometry (ESI MS). Possible complexation of the glycosides with cholesterol was examined. The ichtyotoxic activity of the glycosides and their mixtures with cholesterol to Barbus fefrozona was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…The comparison of the dimensions of CAF molecules with those of zeolite channels and pores: micropores (<1.5 nm) and (ii) mesopores (1.5-16.0 nm), revealed that there were no spatial limitations for the drug molecules to enter the microand mesopores of the zeolitic matrix ( Figure 6). However, a number of scientific investigations revealed the tendency of self-association of CAF molecules, as well as the formation of stable dimers in aqueous solutions, especially at high concentrations [25], involving stacking interactions [26,27]. Consequently, the latter phenomenon could explain the observed lower values of the intraparticle diffusion correlation coefficients and rate constants as compared to those obtained for the PSO model.…”
Section: Host-guest Interactionsmentioning
confidence: 98%
“…The comparison of the dimensions of CAF molecules with those of zeolite channels and pores: micropores (<1.5 nm) and (ii) mesopores (1.5-16.0 nm), revealed that there were no spatial limitations for the drug molecules to enter the microand mesopores of the zeolitic matrix ( Figure 6). However, a number of scientific investigations revealed the tendency of self-association of CAF molecules, as well as the formation of stable dimers in aqueous solutions, especially at high concentrations [25], involving stacking interactions [26,27]. Consequently, the latter phenomenon could explain the observed lower values of the intraparticle diffusion correlation coefficients and rate constants as compared to those obtained for the PSO model.…”
Section: Host-guest Interactionsmentioning
confidence: 98%
“…Использовали программное обеспечение micrOTOFcontrol Ихтиотоксичность проверяли на рыбах Poecilia sphenops (Poeciliidae) по известной методике. [25] Рыб (по 10 штук) помещали в 10 -4 М растворы GC и β-CD, а также в их комплекс, содержащий по 10 -4 М каждого из компонентов. Определяли время инкубации, в течение которого происходил бы 100 % летальный исход.…”
Section: экспериментальная частьunclassified
“…Triterpene glycosides 1 and 2 are characteristic of plants from various species of the genus Hedera L. (ivy) [5] and are ingredients of the cough medicines "Gedeliks" [6,7] and "Prospan" [6,8], which contain extract of H. helix L. leaves. Complexes of 1 with amino acids [9,10], cholesterol [11], and sildenafil [12] were prepared. The reaction of 1 and 2 with caffeine in aqueous solutions was examined [13].…”
mentioning
confidence: 99%